Ultrasound-Histopathological Presentation of Thyroid and Ovary Lesions in Adolescent Patients with DICER1 Syndrome: Case Reports and Literature Overview - Dominika Januś; Monika Kujdowicz; Konrad Kaleta; Kamil Możdżeń; Jan Radliński; Anna Taczanowska-Niemczuk; Aleksandra Kiszka-Wiłkojć; Marcin Maślanka; Wojciech Górecki; Jerzy B. Starzyk (MDPI AG, 2024)
Background: DICER1, a cancer predisposition syndrome (CPS), seems to escape timely diagnosis in pediatric patients. Case report 1: A 16-year-old female patient was referred to the endocrinology ward due to a large goiter. Her medical history indicated normal sexual maturation, with menarche occurring at 13.5 years. Over the past 2.5 years, she had developed pronounced androgenic symptoms, including a deepened male voice; facial, back, and neckline acne; hirsutism; and menstrual irregularities leading to secondary amenorrhea. A thyroid ultrasound identified a multinodular goiter (MNG) with cystic-solid lesions containing calcifications. An abdominal ultrasound identified a 5.7 × 6.9 cm solid mass in the right adnexal region, displacing the uterus to the left. Histopathological examination confirmed a Sertoli-Leydig cell tumor. The patient was subjected to a total thyroidectomy. Histopathology revealed benign follicular cell-derived neoplasms. Thyroid follicular nodular disease (TFND) was diagnosed bilaterally. DNA analysis using NGS, confirmed via the Sanger method, revealed a pathogenic heterozygotic variant c.2953C>T [p.Gln985*] in exon 18 of the DICER1 gene. Case report 2: A 12-year-old male patient was admitted to the pediatric surgery unit due to a 33 mL goiter. A month prior to his admission, the patient discovered a palpable nodule in his neck, accompanied by hoarseness. An ultrasound revealed MNG. Molecular analysis revealed a pathogenic heterozygotic variant c.2782C>T [p.Gln928*] in exon 17 of the DICER1 gene. Subsequently, a total thyroidectomy was performed, and histopathological examination revealed TFND bilaterally. Conclusions: Recent advances in genetic evaluation and in histological approaches indicate that MNG/TFND, although rare in the pediatric population, when accompanied by characteristic ultrasound and histopathological features, and by additional features such as androgenization, may warrant assessment also of the DICER1 gene within CPS molecular panel screening.